Epstein–Barr Virus, But Not Human Papillomavirus, Is Associated With Preinvasive and Invasive Ocular Surface Squamous Neoplasias in Zambian Patients - Julius, Peter; Siyumbwa, Stepfanie N.; Moonga, Phyllis; Maate, Fred; Kaile, Trevor; Haynatski, Gleb; Minhas, Veenu; Snow, Jazmine; Peterson, Kerstin; Gihozo, Patience; Streeter, Sam; Kaur, Salan; et al. (Frontiers in Oncology, 2022)
Background: The etiopathogenesis of ocular surface squamous neoplasia (OSSN) is not fully understood. We assessed the frequency of oncogenic viruses in OSSN by immunohistochemistry (IHC) and polymerase chain reaction (PCR) for human papillomavirus (HPV), Epstein-Barr virus (EBV), Merkel cell virus (MCPyV), Kaposi sarcoma virus, and adenovirus. Cases from Zambia were prospectively enrolled using a cross-sectional study design between November 2017 and March 2020. Methods: Demographic and clinical data (age, sex, HIV status, ART history, CD4 count, plasma viral load), and tumor biopsies were collected from 243 consenting patients. Tumor samples were bisected, and half was used for DNA isolation, while the other half was formalin fixed and paraffin embedded (FFPE) for histopathology analysis. Expression of latent Epstein-Barr virus nuclear antigen 1 (EBNA1), CDKN2A/p16INK4A (p16), and MCPyV large T-antigen (LT) were tested by immunohistochemistry (IHC). Multiplex PCR was used to detect 16 HPV genotypes and four other DNA tumor viruses (KSHV, EBV, MCPyV, and Adenovirus). Relationships between HIV status, viral DNA and protein expression, and tumor grades were determined by statistical analysis. Results: OSSN tumors from patients were 29.6% preinvasive and 70.4% invasive. Patients presented with unilateral tumors which were 70.4% late-stage (T3/T4). OSSN patients were HIV 72.8% positive. IHC on 243 formalin fixed paraffin embedded (FFPE) biopsies resulted in detection of EBNA1 (EBV), p16 high-risk HPV (HR-HPV), and MCPyV LT expression at 89.0%, 4.9% and 0.0%, respectively. EBNA1 was expressed in all grades of preinvasive (CIN1, 100%; CIN2, 85.7%; CIN3, 95.8%; and CIS, 83.8%) and in invasive (89.2%) OSSN. PCR on 178 samples detected EBV, HR-HPV, and MCPyV, at 80.3%, 9.0%, and 13.5% of tumors, respectively. EBV was detected in all grades of preinvasive and invasive OSSN. EBV detection was associated with high HIV viral loads (p = 0.022). HR-HPV was detected in 0.0% CIN1, 0.0% CIN2, 5.6% CIN3, 13.0% CIS and 7.0% invasive OSSN. Conclusions: Our findings of EBV DNA and EBNA1 protein in all the grades of preinvasive and especially invasive OSSN is consistent with a potential causal role for EBV in OSSN. A role of HPV in OSSN was not clearly established in this study.